Cytotoxic and Infection-Controlled Investigations of Novel Dihydropyridine Hybrids: An Efficient Synthesis and Molecular-Docking Studies - Mallikarjuna R. Guda; Grigory. V. Zyryanov; Amit Dubey; Venkata Subbaiah Munagapati; Jet-Chau Wen (Pharmaceuticals, 2023)
A sequence of novel 1,4-dihydropyridines (DHP) and their hybrids was developed using a multicomponent strategy under environmentally benign conditions. In addition, computational studies were performed, and the ligand–protein interactions calculated in different bacteria and two fungal strains. Para-hydroxy-linked DHP (5f) showed the best binding energies of 3.591, 3.916, 8.499 and 6.895 kcal/mol against various pathogens used and other substances received a good docking score. The pathogen resistance potential of the synthesized targets against four bacteria and two fungi showed that whole DHP substances exhibit different levels of resistance to each microorganism. Gram-positive bacteria, which are highly sensitive to all molecules, and the MTCC-1884-encoded fungus strongly rejected the studied compounds compared to comparator drugs. In particular, the 5f candidate showed remarkable antimicrobial activity, followed by the substances 5a, 5b, 5j, 5k and 5l. Furthermore, MIC and MBC/MFC properties showed that 5f had a minimum bacterial concentration of 12.5 μg/mL against E. coli and against two fungal pathogens, with its killing activity being effective even at low concentrations. On the other hand, whole motifs were tested for their cytotoxic activity, revealing that the methoxy and hydroxy-linked compounds (5h) showed greater cytotoxic potency, followed by the two hydroxy linked compounds (5d and 5f). Overall, this synthetic approach used represents a prototype for future nature-favored synthesis methods and these biological results serve as a guide for future therapeutic drug research. However, the computer results play an important role in the further development of biological experiments.